IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH PADA SMA NEGERI 5 BANDA ACEH - Aswanita Usman; Cut Zahri Harun; Murniati AR (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: School based management is one of management concepts which aims to increase the quality of education by giving a broad autonomy to a school. This research aimed to find out the implementation of school based management in State Senior High School 5 Banda Aceh. This research used a qualitative approach with a descriptive method. The techniques of data collection were carried out through interview, observation, and documentation study. The subjects of research were the principal, the vice principal, the teachers, the administrative staffs and the committee of State Senior High School 5 Banda Aceh. The results of research showed that: (1) the implementation of school based management in curriculum affairs was begun from designing vision, mission, school objectives, learning program, division of task, extracuricular and curricular activities, syllabus development, lesson plan, teaching schedule, structure, and academic calendar; (2) student affair has been appropriate to the program, which includes acceptance of new students, activity of student orientation period, determination students in a particular class, students’ attendance and discipline at school eventhough there were still students who were not discipline; (3) in field personnel, the recruitment was still managed by a local government; coaching and professional development of teachers were implemented through training activities, subject teachers’ forum, giving a permission for higher education and doing a supervision; meanwhile, mutation and pensioners were still managed by a local government; (4) financial management was carried out by establishing source of funds and analysing needs, budget allocation, supervision and reporting which invoved school stakeholders; and (5) in terms of relations with the community, it has been run well, and it is directed to achieve school objectives and to do a socialisation about school-based management as an effort to involve a community for its active participation to help school.Keywords: School-based Management and Quality of EducationAbstrak: Manajemen Berbasis Sekolah merupakan salah satu konsep manajemen dalam upaya untuk meningkatkan mutu pendidikan dengan memberikan otonomi luas pada sekolah. Penelitian ini bertujuan untuk mengetahui  pelaksanaan manajemen berbasis sekolah pada SMA Negeri 5 Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan wawancara, observasi dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, wakil kepala sekolah, guru, tata usaha dan komite SMA Negeri 5 Banda Aceh. Hasil penelitian  menunjukkan bahwa: (1) penerapan manajemen berbasis sekolah dalam bidang kurikulum dimulai dari penyusunan visi, misi, tujuan sekolah, program pembelajaran, pembagian tugas, kegiatan ekstrakurikuler, pengembangan silabus, rencana pelaksanaan pembelajaran (RPP), jadwal pengajaran, struktur dan kalender pendidikan; (2) bidang kesiswaan, sudah sesuai dengan program meliputi penerimaan siswa baru, kegiatan masa orientasi siswa, penetapan siswa pada kelas tertentu, kehadiran dan disiplin siswa di sekolah. namun masih adanya siswa yang kurang disiplin; (3) bidang personalia, rekruitmen masih diatur oleh pemerintah daerah, pembinaan dan peningkatan profesional guru dilaksanakan melalui kegiatan pelatihan, MGMP, memberikan izin untuk pendidikan lanjutan dan melakukan supervisi, sedangkan mutasi dan pensiunan juga masih dikelola oleh pemerintah daerah; (4) dalam pengelolaan keuangan dilakukan dengan penetapan sumber dana, menganalisis kebutuhan, alokasi anggaran, pengawasan dan pelaporan dengan melibatkan stakeholder sekolah; dan (5) dalam bidang hubungan dengan masyarakat sudah berjalan dengan baik, diarahkan untuk mencapai tujuan sekolah dan melakukan sosialisasi tentang manajemen berbasis sekolah sebagai upaya melibatkan masyarakat untuk berpartisipasi aktif membantu sekolah.Kata Kunci: Manajemen Berbasis Sekolah dan Mutu Pendidikan